Interpretasi Simultan Jarak Jauh: Pengalaman Indonesia - Diran, Inanti Pinintakasih (Jurnal Penerjemahan, 2020)
The unprecedented Covid-19 Pandemic has transformed the world in more ways than anyone can ever imagine. The strict health protocol, social distancing measures, travel restrictions and work from home policies imposed by governments across the globe have transformed the way meetings and conferences are held. Conventional meetings and conferences involving large numbers of people have been prohibited and moved from onsite to online. Virtual meeting platforms is now the new norm. This move also transforms the way interpreters work. Interpreters now work remotely, and in a virtual setting. Indonesia is not immune to this transformation, and Indonesian interpreters must also quickly shift gear. However, the move also brought along a set of problems, including, limited connectivity, insufficient tools and equipment, atypical communication methods, lack of skillsets, confusions, hesitations, and of course, reluctance. Keywords: Remote Interpreting, virtual presence, quality of interpretation, acoustic shock, fatigue.